Student Learning Activity in PKn Subjects Through Talking Stick Game Method in Class V Sd Negeri 106160 Tanjung Rejo - Ernida Simbolon, Siti (Berpusi Publishing, 2023)
This research was motivated by the low activity of students in expressing opinions and answering teacher questions in class V SD Negeri 106160 Tanjung Rejo, because the method used by the teacher was not attractive. The formulation of the problem found in this study is how active student learning is in Civics before using the talking stick game method, how is student learning active in Civics subjects after using the talking stick game method, and how is student learning activeness increased in Civics subjects by using talking stick game method. The type of research used is classroom action research (PTK) according to Arikunto (Rahakbauw & Watini, 2022). The subjects of this study were 24 students of class V, totaling 24 students. Data collection techniques use research instruments in the form of observation sheets. The results showed that there was an increase in student activity in Civics subjects in class V SD Negeri 106160 Tanjung Rejo. The results of student learning activeness before the talking stick method was applied with 21% completeness. This result did not meet the KKM, namely 70. In the first cycle, completeness increased to 54%, meaning that there was an increase in cycle I, while the results in cycle II experienced another increase, which increased to 83% completeness. Thus the talking stick method can be used as a learning method that can increase student learning activity.